A Systematic Literature Review and Bibliometric Analysis of Developing Music as A Foundation for Health Communication - Dani Fadillah; Sularso Sularso; Zhou Huiqian (Universitas Muhammadiyah Yogyakarta, 2023)
This research will serve as a major source of information for scientists who specialize in the study of health communication, particularly that related to music’s role. This study aims to assess how the field of research on the role of music in health communication has developed. The Scopus database was searched using the keywords “music” and “health communication” to find 904 documents containing this study’s data. After that, the author offers search parameters by only including publications in English-language journals between 2014 and 2022. As a result of these limitations, 300 document results were found that matched the required criteria. The VOSviewer and Bibliometric software were used to process the data. This research found that music has a significant role in health communication, particularly when it comes to issues involving mental health, such as depression, dementia, and anxiety in both adults and children. In the future, this research can be developed regarding how health communication can be developed through media intermediaries other than music.